Designing Research on Variable Ratio for Recirculating Ball Steering Gears with Eccentric Gear Sector - Hou Xunbo; Han Weijie; Wang Xuguang; Ji Shuai; Li Zhenpeng (Jixie chuandong)
In order to realize the variable clearance characteristic, the gear sector on the pitman arm shaft in recirculating ball steering gears is usually set with eccentricity. This eccentric gear sector is also an important component to realize the variable ratio of steering gears. Because of the eccentricity of the gear sector, the output ratio curve of steering gears will be affected, especially the variable ratio curve, and variation will occur. The coordinate system is established based on the geometric center point of the gear sector and the axis point of the pitman arm shaft respectively to calculate and analyze the instantaneous change of the ratio caused by the eccentric gear sector at each corner point. It is proposed to use the expected ratio of the steering gear to subtract the instantaneous change for correction. According to the instantaneous corrected ratio, the tooth profile surface of the eccentric gear sector is designed, which can enable the steering gear to output the expected ratio curve. At the same time, a simplified method for the ration correction ratio is proposed, and the error with the expected value can be controlled within 0.3%.